Trends in and determinants of neonatal mortality and availability and service readiness for newborn care, 2016-2022 Nepal DHS surveys and 2015-2021 Nepal HFS surveys - Narayan Pokhrel, Khem; Khatri, Resham; Pradhan, Gauri; Ram Thapa, Tulsi; Pullum, Tom (ICF, 2024)
For two decades, Nepal has made progress in reducing the neonatal mortality rate (NMR). However, the country has observed a stagnant NMR of 21 neonatal deaths (reported per 1,000 live births) since 2016. Widened equity gaps in NMR exist between socioeconomically disadvantaged and privileged groups. Health facility readiness and delivery of optimal quality newborn care are fundamental for improved health outcomes; however, limited evidence is available on NMR trends and determinants and the readiness of health facilities to deliver newborn care. Therefore, this study examined NMR trends and determinants using data from the 2016 Nepal Demographic and Health Survey (NDHS) and 2022 NDHS, as well as health facility readiness for maternal and newborn health (MNH) care using data from the 2015 Nepal Health Facility Survey (NHFS) and the 2021 NHFS. The study included 106 neonatal deaths (out of 5,087 live births) from the NDHS and 105 neonatal deaths (out of 5,192 live births) from the 2022 NDHS. Independent variables included household-level background characteristics and characteristics related to pregnancy, MNH, women’s empowerment, and health systems. The NMRs for 2016 and 2022 were constructed based on all births in the 5 years preceding the survey. General linear modeling was used to assess significant changes in NMR from 2016 to 2022 by background variables. NMR determinants were identified by conducting logit regression analyses. Further, the World Health Organization’s (WHO’s) service availability and readiness assessment framework was used to examine changes over time in health facility readiness for MNH care based on data from the 2015 and 2021 NHSF surveys. Despite the stagnant NMR since 2016 at the national level in Nepal, an increase in NMR was found across socioeconomically disadvantaged groups and mothers who did not use MNH services. NMR equity gaps widened among advantaged and disadvantaged groups stratified by wealth status, education, and ethnicity. Higher NMRs were observed among newborns if they were from the poorest households, their mothers had no education, and they were from disadvantaged ethnicities, when compared with privileged counterparts. In contrast, NMRs were lower among mothers with higher empowerment status and those who utilized maternal services for their last births, such as deliveries assisted by skilled birth attendants and postnatal checkups for newborns. Despite slight improvements in health facility readiness for delivery and newborn care between 2015 and 2021 at the national level, no improvements were seen in health facilities in Madhesh and Lumbini provinces or in the Terai ecoregion. Health system efforts should include the design and implementation of targeted interventions for disadvantaged groups and improve access to and delivery of MNH care. Peripheral health facilities need to be equipped with essential supplies and ensure that trained health workers are available for essential newborn care. Moreover, the findings call for the expansion of neonatal intensive care units and special newborn care units at higher-level health facilities. A specific survey focusing on neonatal mortality and causes of death is recommended to further examine the determinants after adjusting for covariables and possibly linking with health service readiness.
For assistance using downloaded citations from The DHS Program, please visit http://dhsprogram.com/publications/Citing-DHS-Publications.cfm
This report is a publication of The Demographic and Health Surveys (DHS) Program, which is designed to collect, analyze, and disseminate data on fertility, family planning, maternal and child health, nutrition, and HIV/AIDS. Funding was provided by USAID through The DHS Program (#720-OAA- 18C-00083). The opinions expressed here are those of the authors and do not necessarily reflect the views of USAID or other cooperating agencies.